Fuel cell gas diffusion layer and preparation method and application thereof

By using a microporous layer structure with specific composition in the fuel cell gas diffusion layer, including carbon powder such as Vulcan XC72 and carbon nanotubes such as graphitized nanocarbon fibers, the problem of insufficient hydrothermal management capabilities of the existing fuel cell gas diffusion layer is solved, high porosity and breathability are achieved, and fuel cell performance and process simplicity is improved.

CN119627125AInactive Publication Date: 2025-03-14HUNAN JINBO HYDROGEN ENERGY TECH CO LTD

Patent Information

Application Number
CN202510147498.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing fuel cell gas diffusion layer has limited hydrothermal management capabilities, complex preparation process, and insufficient porosity and breathability of the microporous layer, which affects the performance of the fuel cell.

Method used

Using a microporous layer structure including the first carbon black and the second carbon black, the first carbon black is at least one of Vulcan XC72, Ketjenblack EC-300J and Super P-Li, and the second carbon black is a carbon nanotube and nanocarbon fiber with a graphitization degree of between 90 and 95%, and a gas diffusion layer is prepared by a specific shear treatment and sintering process.

Benefits of technology

The porosity and breathability of the gas diffusion layer of the fuel cell are improved, better hydrothermal management capabilities are achieved, the current density and conductivity of the fuel cell are improved, and the process is simple and easy to mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627125A_ABST
    Figure CN119627125A_ABST
Patent Text Reader

Abstract

The invention provides a fuel cell gas diffusion layer and a preparation method and application thereof, the fuel cell gas diffusion layer comprises a substrate layer and a microporous layer arranged on the surface of the substrate layer, and the microporous layer comprises first carbon black and second carbon black; the first carbon black comprises at least one of Vulcan XC72, Ketjenblack EC-300J and Super P-Li, and the second carbon black comprises at least one of a carbon nanotube and a carbon nanofiber with the graphitization degree of 90-95%; wherein the diameter of the carbon powder is 10-50 nm; the diameter of the carbon nanotube is 2-20 nm, the length of the carbon nanotube is 1-15 [mu] m, and the length-diameter ratio of the carbon nanotube is 100-500; the diameter of the carbon nanofibers is 100-500 nm, the length of the carbon nanofibers is 5-30 [mu] m, and the length-diameter ratio of the carbon nanofibers is 10-100. The gas diffusion layer of the fuel cell has relatively good hydrothermal management capability, and the performance of the fuel cell can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a fuel cell gas diffusion layer material, in particular to a fuel cell gas diffusion layer and a preparation method and application thereof, belonging to the technical field of fuel cells. Background Art

[0002] A fuel cell is an energy conversion device that can directly convert the chemical energy in hydrogen into electrical energy. It has the advantages of high energy conversion efficiency and being clean and pollution-free. It is considered to be one of the effective ways to solve energy shortages and environmental pollution.

[0003] Proton exchange membrane fuel cells are the most widely used type of fuel cells, consisting of membrane electrodes, gas diffusion layers, bipolar plates, and end plates. Among them, the gas diffusion layer is composed of a base layer and a microporous layer, which plays an important role in transmitting gas, discharging water, conducting electrons, and conducting heat. The base layer is generally carbon fiber paper, and the main components of the microporous layer are carbon black and hydrophobic agents. Thanks to the smaller pore size in the microporous layer, the microporous layer can effectively reduce the water saturation, thereby achieving more balanced water management in the gas diffusion layer.

[0004] Chemical grafting is often used to make microporous layers. It is a method of changing the surface properties of materials by grafting functional molecules onto solid surfaces. However, the chemical grafting process is complicated, and the marginal effect during powder grafting makes it difficult to mass produce the process. In addition, the hydrothermal management capability of the microporous layer made by chemical grafting is limited, so it is difficult to further improve the performance of fuel cells by using the microporous layer made by chemical grafting.

[0005] CN117039006A discloses a gas diffusion layer, a fuel cell and a preparation method. The gas diffusion layer of the application includes a first microporous layer, a second microporous layer and a substrate layer, and the second microporous layer includes a second carbon powder and carbon nanotubes. However, the length of the carbon nanotubes will have an important impact on the performance of the gas diffusion layer. Too long carbon nanotubes may cause the structure to be too dense, hindering the flow of gas. In addition, the layered structure in the application causes the diffusion layer to have an additional interface, which will lead to an increase in contact resistance and affect the electron mass transfer efficiency of the battery.

[0006] CN100423338C discloses a gas diffusion layer for a low-temperature fuel cell and a preparation method thereof. The application prepares a microporous layer by mixing a conductive carbon material with a large particle size and a small specific surface area with a conductive carbon material with a small particle size and a large specific surface area. Although the contact resistance can be reduced, the conductive performance of the gas diffusion layer in the application is still not significantly improved.

[0007] Therefore, how to develop a microporous layer that can achieve balanced water management, is beneficial to the electrochemical performance of fuel cells and has a simple preparation process is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0008] In view of the above-mentioned defects, the present invention provides a fuel cell gas diffusion layer, which has high porosity and permeability, is conducive to achieving flexible hydrothermal management of the fuel cell and improving the performance of the fuel cell.

[0009] The present invention provides a method for preparing a fuel cell gas diffusion layer. The method has a simple process and can realize the preparation of the fuel cell gas diffusion layer.

[0010] The present invention provides a fuel cell gas diffusion electrode, which includes the fuel cell gas diffusion layer as described above, and can enable the fuel cell to maintain good performance in a high humidity or low humidity environment.

[0011] The present invention also provides a fuel cell, which includes the fuel cell gas diffusion layer or the fuel cell gas diffusion electrode as described above and has good water heat management capability.

[0012] One aspect of the present invention provides a fuel cell gas diffusion layer, the fuel cell gas diffusion layer comprising a substrate layer and a microporous layer disposed on the surface of the substrate layer, the microporous layer comprising a first carbon black and a second carbon black;

[0013] The first carbon black comprises at least one of carbon powder Vulcan XC72, Ketjenblack EC-300J and Super P-Li, and the second carbon black comprises at least one of carbon nanotubes and nanocarbon fibers with a graphitization degree between 90% and 95%;

[0014] The diameter of the carbon powder is 10-50 nm; the diameter of the carbon nanotube is 2-20 nm, the length is 1-15 μm, and the aspect ratio is 100-500; the diameter of the nano carbon fiber is 100-500 nm, the length is 5-30 μm, and the aspect ratio is 10-100.

[0015] The fuel cell gas diffusion layer as described above, wherein the specific surface area of ​​the carbon powder is 200-500 m 2 / g; the specific surface area of ​​the nano carbon fiber is 10~20 m 2 / g; the specific surface area of ​​the carbon nanotubes is greater than 500 m 2 / g.

[0016] The fuel cell gas diffusion layer as described above, wherein the mass ratio of the first carbon black to the second carbon black is w,0 <w≤1。

[0017] The fuel cell gas diffusion layer as described above, wherein the fuel cell gas diffusion layer further comprises at least one of a leveling agent, a dispersant, and a hydrophobic agent; the mass percentage of the leveling agent in the fuel cell gas diffusion layer is 0.1 to 2 wt%; and / or,

[0018] The mass percentage of the dispersant in the fuel cell gas diffusion layer is 0.5-5 wt%; and / or,

[0019] The mass percentage of the hydrophobic agent in the fuel cell gas diffusion layer is 15-40wt%.

[0020] The present invention also provides a method for preparing a fuel cell gas diffusion layer, comprising the following steps:

[0021] 1) adding a mixture of the first carbon black and the second carbon black to a mother solution including water, alcohol, a leveling agent and / or a dispersant and performing a first shearing treatment, and obtaining a first mixed system after 30 to 120 minutes; and the alcohol in the mother solution is one or more alcohols having a molecular weight of not more than 60 g / mol;

[0022] 2) adding a hydrophobic agent to the first mixed system for a second shearing treatment, and obtaining a microporous layer slurry after 5 to 10 minutes; and the shearing speed of the first shearing treatment is greater than the shearing speed of the second shearing treatment;

[0023] 3) The microporous layer slurry is disposed on the surface of the base layer, and sintered at 360-400° C. for 30-120 min to obtain the gas diffusion layer.

[0024] In the method for preparing a fuel cell gas diffusion layer as described above, in step 1), the volume ratio of water to alcohol is 1:0.1 to 1:1.

[0025] In the method for preparing a fuel cell gas diffusion layer as described above, in step 1), the shearing speed of the first shearing treatment is 6000-10000 rpm.

[0026] The method for preparing a fuel cell gas diffusion layer as described above, wherein in step 2), the shear speed of the second shear treatment is 500-2000 rpm;

[0027] The present invention also provides a fuel cell gas diffusion electrode, comprising the fuel cell gas diffusion layer as described above or the fuel cell gas diffusion layer prepared by the method for preparing the fuel cell gas diffusion layer as described above.

[0028] The present invention also provides a fuel cell, comprising the fuel cell gas diffusion layer or the fuel cell gas diffusion electrode as described above.

[0029] Beneficial effects:

[0030] The fuel cell gas diffusion layer provided by the present invention comprises a base layer and a microporous layer arranged on the surface of the base layer. Compared with the prior art, the present invention further limits the diameter, length, and aspect ratio of the carbon nanotubes and nanocarbon fibers in the second carbon black, so that the microporous layer has a higher porosity and air permeability, further balances the gas diffusion performance and water management performance of the microporous layer, and enables the battery to maintain good water and heat management capabilities in dry environments and humid environments, avoiding "flooding" inside the battery. In addition, when the diameter, length, aspect ratio of the carbon nanotubes and nanocarbon fibers of the fuel cell gas diffusion layer and the degree of graphitization of the nanocarbon fibers meet the conditions of the present invention, the fuel cell exhibits a higher current density, indicating that the fuel cell gas diffusion layer has good electrical conductivity.

[0031] The preparation method of the fuel cell gas diffusion layer provided by the present invention can prepare a fuel cell gas diffusion layer with high porosity and permeability. The fuel cell gas diffusion layer is composed of a base layer and a microporous layer arranged on the surface of the base layer. The microporous layer has high porosity and permeability, so that it can effectively deal with the "flooding" problem inside the battery, which is beneficial to improving the flexible water and heat management capabilities of the battery. In addition, the preparation process of the fuel cell gas diffusion layer is simple, easy to operate, and conducive to mass production.

[0032] The present invention provides a fuel cell gas diffusion electrode, including the fuel cell gas diffusion layer as described above or the fuel cell gas diffusion layer prepared by the preparation method of the fuel cell gas diffusion layer as described above, which can improve the water and heat management ability of the battery and has higher conductivity.

[0033] The fuel cell provided by the present invention comprises the fuel cell gas diffusion layer as described above or the fuel cell gas diffusion electrode as described above, and has flexible water and heat management capability and efficient battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The polarization curve of the fuel cell prepared in Example 1 of the present invention;

[0035] Figure 2 This is the polarization curve of the fuel cell prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] A first aspect of the present invention provides a fuel cell gas diffusion layer, the fuel cell gas diffusion layer comprising a substrate layer and a microporous layer arranged on the surface of the substrate layer, the microporous layer comprising a first carbon black and a second carbon black;

[0038] The first carbon black includes at least one of carbon powder Vulcan XC72, Ketjenblack EC-300J and Super P-Li, and the second carbon black includes at least one of carbon nanotubes and nanocarbon fibers with a graphitization degree between 90% and 95%;

[0039] Among them, the diameter of carbon powder is 10~50 nm; the diameter of carbon nanotubes is 2~20 nm, the length is 1~15μm, and the aspect ratio is 100-500; the diameter of nanocarbon fibers is 100~500 nm, the length is 5~30 μm, and the aspect ratio is 10~100.

[0040] The above-mentioned fuel cell gas diffusion layer, wherein the specific surface area of ​​the carbon powder is 200-500 m 2 / g; the specific surface area of ​​carbon nanotubes is greater than 500 m 2 / g; the specific surface area of ​​nanocarbon fiber is 10~20 m 2 / g.

[0041] The present invention does not limit the material type of the substrate layer, as long as it has good mechanical strength, chemical stability and thermal stability and can stably conduct protons, such as hydrophobic carbon fiber paper. In order to make the fuel cell have good gas exchange capacity, the substrate layer includes pores, and the pore diameter of the pores is 40-100 μm.

[0042] Specifically, the pore size of the substrate layer is 40-100 μm. For example, the pore size of the substrate layer includes but is not limited to 40 μm, 60 μm, 80 μm, 100 μm, or any two thereof. By controlling the pore size within this range, the substrate layer can have good ventilation and is conducive to better water and heat management performance of the fuel cell.

[0043] Specifically, the pore size was tested by scanning electron microscopy and calculated using ImageJ.

[0044] The present invention uses at least one of carbon powder Vulcan XC72, Ketjenblack EC-300J and Super P-Li as the first carbon black, and uses at least one of carbon nanotubes and nano carbon fibers as the second carbon black. For example, Vulcan XC72 is used as the first carbon black, and nano carbon fibers are used as the second carbon black.

[0045] The nano carbon fiber of the present invention is a highly graphitized nano carbon fiber, and the degree of graphitization is 90% to 95%. For example, the degree of graphitization includes but is not limited to 90%, 91%, 92%, 93%, 94%, 95% or the scope of any two of them. In order to enhance the electrical conductivity, strength, rigidity and thermal stability of the fuel cell gas diffusion layer, the graphene and nano carbon fiber in the present invention are highly graphitized graphene and nano carbon fiber. In addition, by adding highly graphitized graphene and nano carbon fiber to the microporous layer slurry, the viscosity of the microporous layer slurry can be controlled, so that the coating process in the fuel cell preparation process is more efficient, to prepare a fuel cell with better performance.

[0046] Specifically, the degree of graphitization can be tested by means of X-ray diffraction (XRD), Raman spectroscopy, transmission electron microscopy (TEM), etc.

[0047] The carbon powder of the present invention is spherical with a diameter of 10-50 nm; the carbon nanotube of the present invention is tubular with a diameter of 2-20 nm, a length of 1-15 μm, and an aspect ratio of 100-500; the graphene of the present invention is flake-shaped with a diameter of 0.5-10 μm; the nano-carbon fiber of the present invention is rod-shaped with a diameter of 100-500 nm, a length of 5-30 nm, and an aspect ratio of 10-100.

[0048] Specifically, the diameter of the carbon powder is 10-50 nm. For example, the diameter of the carbon powder includes but is not limited to 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, or any two thereof. Controlling the carbon powder diameter within this range is beneficial to avoid the carbon powder from forming a dense stacking structure, thereby facilitating the improvement of the porosity and permeability of the fuel cell gas diffusion layer, thereby improving the efficiency of the fuel cell.

[0049] The diameter of the carbon nanotube is 2-20 nm, the length is 1-15 μm, and the aspect ratio is 100-500. For example, the diameter of the carbon nanotube includes but is not limited to 2 nm, 5 nm, 10 nm, 15 nm, 20 nm or any two of them, the length of the carbon nanotube includes but is not limited to 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 12 μm, 15 μm or any two of them, and the aspect ratio of the carbon nanotube includes but is not limited to 100, 200, 300, 400, 500 or any two of them. On the one hand, longer carbon nanotubes can form a more complex network, resulting in an increase in porosity and permeability; on the other hand, thinner carbon nanotubes will form more carbon nanotube networks in the same volume, thereby increasing the number of pores, but if the diameter is too low, it may cause the aggregation of carbon nanotubes, resulting in a decrease in porosity. In addition, a larger diameter is also conducive to improving permeability. Therefore, by limiting the diameter, length, and aspect ratio of carbon nanotubes, the porosity and permeability of the microporous layer of the fuel cell can be improved, thereby improving the hydrothermal management capability of the fuel cell.

[0050] The diameter of the nanocarbon fiber is 100-500 nm, the length is 5-30 nm, and the aspect ratio is 10-100. For example, the diameter of the nanocarbon fiber includes but is not limited to 100nm, 200nm, 300nm, 400nm, 500nm or any two of them, the length of the carbon nanotube includes but is not limited to 5nm, 10nm, 15nm, 20nm, 25nm, 30nm or any two of them, and the aspect ratio of the carbon nanotube includes but is not limited to 10, 30, 50, 70, 80, 100 or any two of them. When the nanocarbon fiber is applied to the fuel cell, its diameter and length need a balanced range. On the one hand, when the diameter of the nanocarbon fiber is small, it is conducive to increasing the porosity, while when the diameter is too small, it will cause the aggregation of the nanocarbon fiber and cause the porosity to decrease, and the larger diameter is also conducive to improving the permeability; on the other hand, the longer nanocarbon fiber can provide a complex network, thereby increasing the porosity and permeability. Therefore, controlling the diameter, length and aspect ratio of the nanocarbon fiber within this range is conducive to improving the porosity and permeability of the fuel cell gas diffusion layer. Therefore, by limiting the diameter, length, and aspect ratio of carbon nanotubes, the porosity and permeability of the microporous layer of the fuel cell can be improved, thereby improving the hydrothermal management capability of the fuel cell.

[0051] The present invention effectively improves the porosity and permeability of the fuel cell gas diffusion layer by adjusting the material composition of the microporous layer and the substrate layer of the fuel cell gas diffusion layer, which is beneficial to the rapid diffusion of fuel and oxidant (such as hydrogen and oxygen) on the electrodes in the fuel cell, thereby improving the hydrothermal management performance of the fuel cell.

[0052] In a specific embodiment, the specific surface area of the carbon powder is 200 - 500 m 2 / g, the specific surface area of the carbon nanotubes is greater than 500 m 2 / g, and the specific surface area of the nanofiber carbon is 13 m 2 / g. Keeping the specific surface areas of the carbon powder, carbon nanotubes, graphene, and nanofiber carbon within this range is beneficial to increasing the porosity and air permeability of the fuel cell gas diffusion layer.

[0053] In a specific embodiment, the mass ratio of the first carbon black to the second carbon black is w, where 0 < w ≤ 1. For example, w includes but is not limited to 0.01, 0.1, 0.3, 0.5, 0.7, 0.9, 1, or the range composed of any two of them. Controlling the mass ratio of the first carbon black to the second carbon black within the above range is beneficial to preparing a fuel cell gas diffusion layer with better performance.

[0054] In addition, the fuel cell gas diffusion layer further includes at least one of a leveling agent, a dispersant, and a hydrophobic agent.

[0055] In one embodiment, the mass percentage of the leveling agent in the fuel cell gas diffusion layer is 0.1 - 2 wt%. For example, the mass percentage of the leveling agent in the fuel cell gas diffusion layer includes but is not limited to 0.1 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, or the range composed of any two of them. Controlling the mass percentage of the leveling agent within the above range is beneficial to preparing a fuel cell gas diffusion layer with higher porosity and air permeability, enhancing the mass transfer efficiency inside the electrode, and thus preparing a fuel cell gas diffusion layer with better performance.

[0056] In another embodiment, the mass percentage of the dispersant in the fuel cell gas diffusion layer is 0.5 - 5 wt%. For example, the mass percentage of the dispersant in the fuel cell gas diffusion layer includes but is not limited to 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, or the range composed of any two of them. Controlling the mass percentage of the dispersant within the above range is beneficial to preparing a fuel cell gas diffusion layer with higher porosity and air permeability, enhancing the mass transfer efficiency inside the electrode, and thus preparing a fuel cell gas diffusion layer with better performance.

[0057] In another embodiment, the mass percentage of the hydrophobic agent in the fuel cell gas diffusion layer is 15-40%. For example, the mass percentage of the hydrophobic agent in the fuel cell gas diffusion layer includes but is not limited to 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or any two thereof. By controlling the mass percentage of the hydrophobic agent within the above range, it is beneficial to prepare a fuel cell gas diffusion layer with high porosity and permeability, enhance the mass transfer efficiency inside the electrode, and thus prepare a fuel cell gas diffusion layer with better performance.

[0058] The present invention does not limit the type of leveling agent, for example, the leveling agent in the present invention can be at least one of carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and sodium hydroxymethyl cellulose. In order to adjust the fluidity of the material, the present invention adds a leveling agent so that the material can quickly form a uniform and smooth surface after coating or molding.

[0059] The present invention also does not limit the type of dispersant. For example, the dispersant in the present invention can be at least one of sodium stearate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol ether sulfate. The present invention changes the rheological properties of the material and stabilizes the dispersion system by adding a dispersant, so that the components in the prepared gas diffusion layer are distributed more evenly, the quality of the fuel cell gas diffusion layer is improved, and thus it is beneficial to improve the quality of the fuel cell.

[0060] A second aspect of the present invention provides a method for preparing a fuel cell gas diffusion layer, comprising the following steps:

[0061] 1) adding a mixture of a first carbon black and a second carbon black to a mother solution including at least one of water and alcohol, a leveling agent and / or a dispersant and performing a first shearing treatment, and obtaining a first mixed system after 30 to 120 minutes; and the alcohol in the mother solution is one or more alcohols having a molecular weight of not more than 60 g / mol;

[0062] 2) adding a hydrophobic agent to the first mixed system for a second shearing treatment, and obtaining a microporous layer slurry after 5 to 10 minutes; the shearing speed of the first shearing treatment is greater than the shearing speed of the second shearing treatment;

[0063] 3) The microporous layer slurry is placed on the surface of the substrate layer, and sintered at 360-400° C. for 30-120 min to obtain a fuel cell gas diffusion layer.

[0064] Specifically, in step 1), the present invention does not limit the mixing method of the mixture of the first carbon black and the second carbon black, as long as the two can be mixed evenly.

[0065] The present invention does not limit the temperature of the first shearing treatment, and it can be adjusted according to actual conditions.

[0066] In the present invention, the time for the first mixing system to undergo the first shear treatment is 30 to 120 min. For example, the time for the first mixing system to undergo the first shear treatment includes but is not limited to 30 min, 60 min, 90 min, 120 min, or a range consisting of any two of these.

[0067] In the present invention, the alcohol is one or more alcohols having a molecular weight of no more than 60 g / mol. For example, the alcohol in the present invention may be one or more of methanol, ethanol, n-propanol, and isopropanol.

[0068] The mother solution of the present invention comprises water, alcohol, a leveling agent and / or a dispersant.

[0069] The present invention also does not limit the mixing method of water and alcohol with the leveling agent. The leveling agent can be added to water and alcohol, or water and alcohol can be added to the leveling agent.

[0070] The present invention also does not limit the mixing method of water, alcohol and dispersant. The dispersant can be added to water and alcohol, or added to the leveling agent.

[0071] In step 2), the present invention does not limit the temperature of the second shearing treatment, and it can be adjusted according to actual conditions.

[0072] In the present invention, the time for adding the hydrophobic agent to the second mixed system for the second shear treatment is 5 to 10 minutes. For example, the time for adding the hydrophobic agent to the second mixed system for the second shear treatment includes but is not limited to 5 minutes, 8 minutes, 10 minutes or a range composed of any two thereof.

[0073] The present invention also does not limit the type of hydrophobic agent. For example, the hydrophobic agent in the present invention includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, and fluorinated ethylene propylene copolymer. The use of a hydrophobic agent can help control moisture and maintain appropriate humidity inside the battery, thereby optimizing the hydrothermal management of the battery.

[0074] In order to disperse the various materials in the microporous layer slurry more evenly, the shear speed of the first shear treatment in the present invention is greater than the shear speed of the second shear treatment. The main purpose of the first shear treatment is to achieve the initial dispersion of the material. The high speed helps to quickly break the agglomeration state of the material and disperse the particles. The high speed can also provide a larger shear force, which helps to overcome the attraction between the materials and promote the separation of the particles. The goal of the second shear stage is to further refine the dispersion and make the material reach a more uniform state. Reducing the speed can reduce the possibility of over-shearing, avoid excessive material crushing or unnecessary heat generation, and ensure that the material is more evenly dispersed.

[0075] In step 3), the microporous layer slurry is placed on the surface of the base layer, and sintered at 360-400° C. for 30-120 min to obtain a fuel cell gas diffusion layer.

[0076] The present invention does not limit the method of disposing the microporous layer slurry on the surface of the base layer. For example, the microporous layer slurry can be disposed on the surface of the base layer by coating.

[0077] The present invention does not specifically limit the base layer, as long as it can be used to coat the microporous layer slurry. In a specific embodiment, the microporous layer slurry can be coated on the surface of the carbon fiber paper after hydrophobic post-treatment, wherein the pore size of the carbon fiber paper is between 0.1 and 50 μm, and the average pore size of the carbon fiber paper is within the above range.

[0078] The present invention does not limit the sintering atmosphere as long as it does not react with the microporous layer slurry. For example, nitrogen can be used as the sintering atmosphere.

[0079] The sintering temperature is 360~400℃. For example, the sintering temperature includes but is not limited to 360℃, 370℃, 380℃, 390℃, 400℃ or a range consisting of any two thereof. The sintering time is 30~120 min. For example, the sintering time includes but is not limited to 30min, 50min, 70min, 90min, 110min, 120min or a range consisting of any two thereof.

[0080] In a specific embodiment, the volume ratio of water to alcohol is 1:0.1 to 1:1. For example, the volume ratio of water to alcohol includes but is not limited to 1:0.1, 1:0.3, 1:0.5, 1:0.7, 1:0.9, 1:1 or any two thereof. By controlling the ratio of water to alcohol in the first mother liquor, the mixing of the first carbon black and the second carbon black is facilitated.

[0081] In a specific embodiment, the shearing speed of the first shearing treatment is 6000-10000 rpm; and / or, the shearing speed of the second shearing treatment is 500-2000 rpm. For example, the shearing speed of the first shearing treatment includes but is not limited to 6000, 7000, 8000, 9000, 10000 or a range consisting of any two thereof; for example, the shearing speed of the second shearing treatment includes but is not limited to 500, 1000, 1500, 2000 or a range consisting of any two thereof. Controlling the shearing speeds of the first shearing treatment and the second shearing treatment within the above range is conducive to a more uniform dispersion of the various material components in the microporous layer slurry.

[0082] The fuel cell gas diffusion layer prepared by the preparation method of the fuel cell gas diffusion layer provided by the present invention has high porosity and air permeability, which is beneficial to the improvement of the hydrothermal management capability of the fuel cell. In addition, the preparation method is simple, the reaction conditions are easy to control, and mass production is easy to achieve.

[0083] The third aspect of the present invention provides a fuel cell gas diffusion electrode, comprising the above-mentioned fuel cell gas diffusion layer or a fuel cell gas diffusion layer prepared by the above-mentioned fuel cell gas diffusion layer preparation method. The fuel cell gas diffusion electrode can improve the water heat management capability of the fuel cell.

[0084] The present invention also provides a fuel cell, comprising the fuel cell gas diffusion layer or fuel cell gas diffusion electrode. The fuel cell exhibits good water and heat management capabilities and can maintain good stability in high humidity and low humidity environments.

[0085] In a specific embodiment, the fuel cell further includes a membrane electrode, an anode catalyst layer, a cathode catalyst layer, and a proton membrane.

[0086] The present invention does not impose any special restrictions on the type of membrane electrode, and any membrane electrode may be selected according to actual conditions.

[0087] The present invention does not limit the effective area of ​​the membrane electrode, which can be set according to needs. For example, the effective area of ​​the membrane electrode can be 5×5 cm 2 .

[0088] The present invention does not limit the type and loading of the metal used in the anode catalyst layer, which can be set according to the needs. For example, the anode catalyst layer can use metal platinum, and the platinum loading can be 0.1 mg / cm 2 .

[0089] The present invention does not limit the type and loading of the metal used in the cathode catalyst layer, which can be set according to the needs. For example, the cathode catalyst layer can use metal platinum, and the platinum loading can be 0.4 mg / cm 2 .

[0090] The present invention does not limit the type of proton membrane, and the proton membrane can be specifically configured as required. For example, DuPont Nafion 211 membrane can be selected as the proton membrane.

[0091] Hereinafter, the present invention will be further described in detail through specific examples.

[0092] Example 1

[0093] The preparation process of the fuel cell gas diffusion layer provided in this embodiment includes the following steps:

[0094] 1) 500 mL of ultrapure water was mixed with 500 mL of ethanol, and then 1 g of sodium hydroxymethyl cellulose was added as a leveling agent (the mass percentage in the fuel cell gas diffusion layer was 0.7 wt%) and 1.5 g of sodium dodecylbenzene sulfonate was added as a dispersant (the mass percentage in the fuel cell gas diffusion layer was 1.05 wt%), and the mixture was stirred evenly with a glass rod to obtain a mother liquor, and then the first carbon black and the second carbon black were added to the mother liquor and subjected to a first shearing treatment to obtain a first mixed system. The first carbon black was carbon powder XC-72R with a mass of 50 g, the second carbon black was nanocarbon fiber with a mass of 50 g, and the mass ratio of the first carbon black to the second carbon black was 1; the shearing speed was 8000 rpm, and the shearing time was 60 min.

[0095] 2) Add 40 g of hydrophobic agent polytetrafluoroethylene to the above-mentioned first mixed system (the mass percentage of the hydrophobic agent in the fuel cell gas diffusion layer is 28.1%; the mass ratio of the total mass of the first carbon black and the second carbon black to the above-mentioned hydrophobic agent is 1:0.4) and perform a second shearing treatment at a shearing speed of 500 rpm and a shearing time of 5 min to obtain a microporous layer slurry.

[0096] 3) The microporous layer slurry is coated on the surface of the carbon fiber paper after hydrophobic post-treatment, the average pore size of the carbon fiber paper is 20 μm, and sintered at 360 ° C for 60 min in a nitrogen atmosphere to obtain a fuel cell gas diffusion layer.

[0097] The carbon powder has a diameter of 30nm and a specific surface area of ​​254m 2 / g; the diameter of nanocarbon fiber is 200nm, the length is 10μm, the aspect ratio is 50, and the specific surface area is 13m 2 / g, the graphitization degree of nanocarbon fiber is 93%; the pore size of carbon fiber paper after hydrophobic post-treatment is 80μm.

[0098] Example 2

[0099] The preparation method of the fuel cell gas diffusion layer provided in this embodiment is basically the same as that in embodiment 1, except that the second carbon black in step 1) is carbon nanotubes with a mass of 50 g.

[0100] The carbon nanotubes have a diameter of 12 nm, a length of 5 μm, an aspect ratio of 416, and a specific surface area of ​​628 m 2 / g.

[0101] Example 3

[0102] The preparation method of the fuel cell gas diffusion layer provided in this embodiment is basically the same as that in Example 1, except that in step 1), the first carbon black is carbon powder XC-72R with a mass of 80 g, the second carbon black is highly graphitized nanocarbon fiber with a mass of 20 g, and the mass ratio of the first carbon black to the second carbon black is 4.

[0103] Example 4

[0104] The preparation method of the fuel cell gas diffusion layer provided in this embodiment is basically the same as that in embodiment 1, except that in step 1), the diameter of the nano-carbon fiber is 100 nm, the length is 5 μm, and the aspect ratio is 50.

[0105] Example 5

[0106] The method for preparing a fuel cell gas diffusion layer provided in this embodiment is basically the same as that in embodiment 1, except that in step 1), the carbon nanotubes have a diameter of 20 nm, a length of 2 μm, and an aspect ratio of 100.

[0107] Comparative Example 1

[0108] The preparation method of the fuel cell gas diffusion layer provided in this comparative example is basically the same as that in Example 1, except that only the first carbon black is added to the mother liquid, and the first carbon black is XC-72R with a mass of 100 g.

[0109] Comparative Example 2

[0110] The preparation method of the fuel cell gas diffusion layer provided in this comparative example is basically the same as that in Example 1, except that in step 1), the diameter of the nano-carbon fiber is 100 nm and the length is 40 μm.

[0111] Comparative Example 3

[0112] The preparation method of the fuel cell gas diffusion layer provided in this comparative example is basically the same as that in Example 1, except that in step 1), the carbon nanotubes have a diameter of 20 nm and a length of 20 μm.

[0113] Comparative Example 4

[0114] The preparation method of the fuel cell gas diffusion layer provided in this comparative example is basically the same as that in Example 1, except that in step 1), the second carbon black is graphene with a mass of 50 g.

[0115] The graphene has a diameter of 3 μm and a specific surface area of ​​325 m 2 / g.

[0116] Comparative Example 5

[0117] The preparation method of the fuel cell gas diffusion layer provided in this comparative example is basically the same as that of comparative example 4, except that the diameter of the graphene is 12 μm.

[0118] Comparative Example 6

[0119] The preparation method of the fuel cell gas diffusion layer provided in this comparative example is basically the same as that of comparative example 1, except that the diameter of the graphene is 8 μm.

[0120] Test example

[0121] The proton exchange membrane fuel cell was assembled with the gas diffusion layer of the fuel cell of the above embodiment and comparative example for testing, wherein the effective area of ​​the membrane electrode was 5×5 cm 2 The anode catalyst layer is made of metal platinum, and the platinum loading is 0.1 mg / cm 2 The cathode catalyst layer is made of metallic platinum with a platinum loading of 0.4 mg / cm 2 , DuPont Nafion211 membrane is selected as the proton membrane. The battery operating temperature is 80 ℃, hydrogen is introduced into the anode side and air is introduced into the cathode side, and the intake volume is set to a stoichiometric ratio of 1.2 and 2.5 respectively. The gases on both sides need to be humidified externally before entering the battery. The intake humidity is controlled at 100 RH% under high humidity conditions and 50 RH% under low humidity conditions.

[0122] By testing the voltages of Example 1 and Comparative Example 1 at different current densities, the polarization curve of the fuel cell can be obtained. The polarization curve of Example 1 is shown in FIG. Figure 1 As shown, the polarization curve of Comparative Example 1 is as follows Figure 2 As shown. Figure 1 as well as Figure 2 It can be seen that by adding highly graphitized carbon nanofibers to the gas diffusion layer of the fuel cell, the fuel cell in Example 1 did not show a significant decrease in potential under high current density and high humidity conditions compared with the battery under low humidity conditions with the same current density, showing good water and heat management capabilities and improving battery performance. -2 When the humidity is 100%, the potential of the battery is significantly lower than that of the battery under 50% humidity, indicating that its thermal management ability is poor. The porosity and permeability test method is GB / T 20042.3-2022: "Proton Exchange Membrane Fuel Cell Part 3: Proton Exchange Membrane Test Method". The porosity and permeability of the fuel cell gas diffusion layer in Examples 1-5 and Comparative Examples 1-6 were tested using the above national standard, and the test results are shown in Table 1.

[0123] The potential of the fuel cells assembled in Examples 1-5 and Comparative Examples 1-6 under different working conditions was tested using a fuel cell test bench. The test results are shown in Table 1.

[0124]

[0125] It can be seen from the test results of the embodiments of the present invention and the comparative examples that:

[0126] 1. The performance of the fuel cell assembled by the fuel cell gas diffusion layer in Examples 1-5 is better than that in Comparative Examples 1-6.

[0127] 2. Adding highly graphitized nanocarbon fibers as the second carbon black can enhance the drainage capacity of the fuel cell gas diffusion layer more than adding carbon nanotubes or graphene as the second carbon black.

[0128] 3. Nanocarbon fibers with lower specific surface area and lower aspect ratio are more effective in alleviating battery "flooding".

[0129] 4. By using high-quality nano-carbon fibers as the second carbon black, the water-heat management capability of the fuel cell can be improved, alleviating battery "flooding".

[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A fuel cell gas diffusion layer, characterized in that: It includes a base layer and a microporous layer arranged on the surface of the base layer, wherein the microporous layer includes a first carbon black and a second carbon black; The first carbon black comprises at least one of carbon powder Vulcan XC72, Ketjenblack EC-300J and Super P-Li, and the second carbon black comprises at least one of carbon nanotubes and nanocarbon fibers with a graphitization degree between 90% and 95%; The carbon powder has a diameter of 10-50 nm; the carbon nanotube has a diameter of 2-20 nm, a length of 1-15 μm, and an aspect ratio of 100-500; the carbon nanofiber has a diameter of 100-500 nm, a length of 5-30 μm, and an aspect ratio of 10-100.

2. The fuel cell gas diffusion layer according to claim 1, characterized in that: The specific surface area of ​​the carbon powder is 200-500 m 2 / g; the specific surface area of ​​the carbon nanotubes is greater than 500 m 2 / g; the specific surface area of ​​the nano carbon fiber is 10~20 m 2 / g.

3. The fuel cell gas diffusion layer according to claim 1 or 2, characterized in that: The mass ratio of the first carbon black to the second carbon black is w, <w≤1。 4. The fuel cell gas diffusion layer according to claim 1 or 2, characterized in that: The fuel cell gas diffusion layer further comprises at least one of a leveling agent, a dispersant, and a hydrophobic agent; The mass percentage of the leveling agent in the fuel cell gas diffusion layer is 0.1-2 wt%; and / or, The mass percentage of the dispersant in the fuel cell gas diffusion layer is 0.5-5 wt%; and / or, The mass percentage of the hydrophobic agent in the fuel cell gas diffusion layer is 15-40wt%.

5. A method for preparing a fuel cell gas diffusion layer according to claim 1 or 2, characterized in that: The following steps are involved: 1) adding a mixture of the first carbon black and the second carbon black to a mother solution including water, alcohol, a leveling agent and / or a dispersant and performing a first shearing treatment, and obtaining a first mixed system after 30 to 120 minutes; and the alcohol in the mother solution is one or more alcohols having a molecular weight of not more than 60 g / mol; 2) adding a hydrophobic agent to the first mixed system for a second shearing treatment, and obtaining a microporous layer slurry after 5 to 10 minutes; and the shearing speed of the first shearing treatment is greater than the shearing speed of the second shearing treatment; 3) The microporous layer slurry is disposed on the surface of the base layer, and sintered at 360-400° C. for 30-120 min to obtain the gas diffusion layer.

6. The method for preparing a fuel cell gas diffusion layer according to claim 5, characterized in that: The volume ratio of water to alcohol is 1:0.1 to 1:

1.

7. The method for preparing a fuel cell gas diffusion layer according to claim 5, characterized in that: The shearing speed of the first shearing treatment is 6000~10000 rpm.

8. The method for preparing a fuel cell gas diffusion layer according to claim 5, characterized in that: The shearing speed of the second shearing treatment is 500-2000 rpm.

9. A fuel cell gas diffusion electrode, characterized in that: A fuel cell gas diffusion layer comprising the fuel cell gas diffusion layer described in any one of claims 1 to 5 or a fuel cell gas diffusion layer prepared by the preparation method of the fuel cell gas diffusion layer described in any one of claims 6 to 8.

10. A fuel cell, characterized in that: The fuel cell gas diffusion layer comprises the fuel cell gas diffusion layer according to any one of claims 1 to 5 or the fuel cell gas diffusion electrode according to claim 9.

Citation Information

Patent Citations

  • Gas diffusion layer for low temp fuel cell and preparing process thereof

    CN100423338C

  • Gas diffusion layer for proton exchange membrane fuel cells and preparation method thereof

    CN101771155A

  • Preparation method of hydrogen fuel cell gas diffusion layer

    CN112490454A

  • Environment-friendly fuel cell gas diffusion layer and preparation method thereof

    CN112563516A

  • Gas diffusion layer, membrane electrode assembly, and fuel cell

    CN112740446A

Cited By

  • Hydrophilic gas diffusion layer and preparation method thereof

    CN122214903A